Social Reflection in Bhaiṣajyavastu of The Scripture of Mūlasarvāstivāda - Sawangsri, Pattama; Sawangsri, Seksan (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Mūlasarvāstivādavinayavastu- Bhaiṣajyavastu Scripture is regarded as a scripture that compiles a history of Buddhism which happened after the 8th century of Buddhism. However, the scripture does not indicate obviously where it happened or who the author was. Therefore, most of the prose in the scripture was written in Classical Sansakrit language, while poems and incantations were mostly written in Hybrid Sansakrit language. The important content of the scripture referred to medicine that the monks were allowed to use. Although the Mūlasarvāstivādavinayavastu - Bhaiṣajyavastu Scripture is mostly about the history of Buddhism, there appeared stories in the scripture included important information about that century which was a great source of information to study and retrieve the history of that century. The stories found in the Mūlasarvāstivādavinayavastu - Bhaiṣajyavastu Scripture reflected on the ways of living in the time of the Buddha, or after the time of Buddha, which was governed by following a monarchy system which consisted of Absolute Monarchy and Limited monarchy. What is more is that it appears that an Oligarchy system was used in that century also. Furthermore, the social system has shown that there was a caste system, a slavery system, and women were more acceptable according to their social status.